Evaluation of the practical performance of fourth-year students in the applied subject in the departments of Physical Education and sports sciences in the colleges of basic education - Yasser Mahmoud Wahib; Mohammad Jaafar Majeed; Murooj t ahseen jaeid (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Objective: The objective of this study is to develop an evaluation form for the practical performance of fourth-year students from the departments of Physical Education and Sports Sciences. Instructors (educational supervisors and scientists) will use this form to grade the subject of application in the faculties of basic education.